Fractures and Fanconi Syndrome due to Prolonged Sodium Valproate Use - Dhillon, N.; Högler, W. (Neuropediatrics, 2011)
Sodium valproate (VPA) is commonly used to treat epilepsy in children. Renal dysfunction is a rare side effect but can present as tubulopathy such as Fanconi syndrome.We report on an 8-year-old disabled girl with myoclonic epilepsy who was referred for investigation of recurrent low impact fractures of the distal femur which were initially thought to be caused by her severe immobility. However, she was subsequently found to have hypophosphataemia secondary to Fanconi syndrome due to prolonged VPA use. After VPA withdrawal renal function and serum phosphate levels normalised and X-rays improved dramatically.The possibility of drug-induced osteoporosis and fractures should always be considered in disabled children, even in the presence of severe immobility.
Keywords: sodium valproate; Fanconi syndrome; hypophosphataemic rickets; fractures; immobility